Riesgo de desarrollar diabetes mellitus tipo 2 mediante el Test de Findrisk en las personas que acuden a Consulta Externa en el Centro de Salud del cantón Zapotillo. - Rodríguez Soto, Jaime Alfredo (2017)
Type 2 Diabetes Mellitus (DM2) is defined as a “metabolic disorder of multiple aetiology is characterized by chronic hyperglycaemia with disorders in the metabolism of the carbohydrates, fats and proteins, which results from disorders in the secretion and / or the action of insulin”. The present research work which is of type prospective, descriptive and transversal; has the general objective: for determining the risk of developing the Type 2 Diabetes Mellitus by means of the FINDRISK Test on people who attend the Outpatient Consultation in the Health Center of Canton Zapotillo; and as specific objectives: to know the risk of developing Type 2 Diabetes Mellitus, to identify leading risk factors that affect the population and to disseminate an educational plan for the prevention of the Diabetes. The questionnaire FINDRISK Test was applied to 348 patients encountering that the 41.38% of the total respondents have a low risk, the 33.62% very low risk, the 12.93% medorate risk, the 11.20% high risk and the 0.87% very high risk. We may therefore conclude that the risk of developing Type 2 Diabetes Mellitus in the next ten years is low but not least important since it may be modified, by the same negative changes in the lifestyles that may arise. Keywords: Type 2 Diabetes Mellitus, Population at Risk, FINDRISK Test.